ADSORPSI LOGAM BERAT SENG (Zn) DENGAN MENGGUNAKAN AKAR RAMBUT Solanum nigrum L GALUR A4 KERING TERIMOBILISASI DALAM Na-alginat - Nastiti Siswi Indrasti, Muhammad Ahkam Subroto dan Gun Gun Gunawan (Jurnal Teknologi Industri Pertanian, 2005)
ABSTRACTRoot tissue of Solanum nigrum L A4 strain was found to adsorb heavy metal especially Zinc (Zn).  Compared with activated carbon used as adsorbent on industrial waste water treatment process, the adsorption by root tissue of Solanum nigrum L was higher. The adsorption of Solanum nigrum L was represented by Langmuir and Freundlich isotherms equation. Ground powder of Solanum nigrum L was immobilized by natrium alginate for a practical use.  Zinc  concentration adsorbed by immobilized Solanum nigrum L were higher than ground powder form.  The adsorption capacity shows the capacity of the adsorbent used.  It was calculated through dividing adsorbat (mg) with the weight of the adsorbent (gr).  Even the concentration of zinc  adsorbed by immobilized beads was higher, the adsorption capacity of ground powder form of Solanum nigrum L was higher then immobilized beads.  It might be caused by the natrium alginate which also adsorbed zinc and formed higher weight of adsorbent, and implies that polymer used for immobilization creates a binding coated on the Solanum nigrum L  ground powder surface.Key words : adsorption, plant tissue, zinc, immobilization